Kriminalisasi Kebijakan Pejabat Negara Dalam Perspektif Tindak Pidana Korupsi - Suratno, Ujang (Yustitia, 2011)
In doing its duty, the government has power related to : (1) the making of law and policies under the law (2) define beschikking which is individual, concrete and final (3) the real and active administration actions, and (4) freis ermessen, wether beleid or dicretion. All actions above are included in state administration action. But, that can be categorized as a corruption when there is materele wederechtelijkheid indication, detournament de povouir and abus de droit.